Career success: don't take it for granted! - Universiti Putra Malaysia, Research Management Centre (Research Management Centre, Universiti Putra Malaysia, 2009)
Career is one of the sites to see the differential dynamics of employees in any organization. It is simply about interaction of an individual, job and organization, even though it is commonly understood as a sequence of jobs in a life-span of an individual. The outcome of a career is career success, and it is indeed created; hence, we don't take it for granted!